ANALISIS PERAN INDONESIA DALAM KERJASAMA DENGAN SINGAPURA DALAM PENETAPAN KAWASAN SPESIAL ECONOMIC ZONE DI WILAYAH BINTAN KARIMUN - Gadis Prasiska; Kania Nova Ramadhani, Muthi’ah lathifah, Putri Widia Ningsih, Reylan Silverius, Salwa Andini, Talita (CV. Adiba Aisha Amira, 2023)
Special Economic Zones (KEK) in Indonesia are an important means of supporting economic growth and investment in several regions. As the global economy becomes more integrated and competitive, cooperation between countries that form special economic zones becomes increasingly important. An example of significant cooperation is between Indonesia and Singapore in the development of special economic zones in the Batam, Bintan and Karimun areas (abbreviated as Riau Islands). This research aims to analyze Indonesia's role in economic cooperation involving the Batam, Bintan and Karimun regions. In the context of this research, the literature study method was used to explore various information and views regarding Indonesia's role in this collaboration. The research results show that Indonesia plays an important role in developing these regions as economic and investment centers. In an effort to increase investment attractiveness, Indonesia has launched various policy incentives, including ease of doing business and investment, which support the growth of the industrial and trade sectors in the region. Apart from that, Indonesia also plays a role in developing regional infrastructure and connectivity that supports this collaboration. Although there are still several challenges that need to be overcome, Indonesia's efforts in collaborating with Batam, Bintan and Karimun have made a positive contribution to economic growth and investment in the region, as well as opening opportunities for further cooperation with neighboring countries.